Biblical Theology of prayer in the New Testament - Francois P, Francois P (Reformed Theology in Africa Series, 2023)
This publication deals with a biblical theology of prayer based on the New Testament. It forms the second of a two-volume publication on a biblical theology of prayer, dealing with the concept of prayer in the Old and New Testament, respectively. This New Testament volume begins with an introduction on prayer and worship in early Jewish tradition, followed by eleven chapters dealing with New Testament corpora. It concludes with a final chapter synthesising the findings of the respective investigations of the Old and New Testament corpora to provide a summative theological perspective of the development of the concept of prayer through scripture. Prayer forms a major and continuous theme throughout the biblical text. Prayer was an integral part of the religious existence of God’s people in both the Old and New Testament. It underwent its greatest developments during, after and as a result of the Exile and was deepened and transformed in the New Testament. In both the Old and the New Testament, God is the sole ‘addressee’ of his people’s prayer. This conviction continued into the New Testament, but was broadened with Trinitarian elements of worship, adoration and intercession. A biblical theological investigation is chosen as methodology. Since all the biblical books form part of one canonical text, the assumption is that the various theologies about prayer being displayed in these books can be synthesised into a developing meta-theology about prayer. As the Old and New Testament form part of the canonical text, the results about prayer in the Old Testament can be brought into play with the results about prayer in the New Testament. This eventually leads toward an overarching biblical theology of prayer